The Effect of Principal’s Leadership and Digital-Based Strategic Implementation on Competency Improvement - Meilani, Hana; Ahyani, Nur; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2024)
The purpose of this study was to determine the effect of principal leadership and the implementation of strategic digital-based school management on improving teachers' pedagogical competence at SMP Negeri 1 Koba, Central Bangka Regency. The sample size taken was 40 teachers from SMP Negeri 1 Koba, Central Bangka Regency. The sampling technique was saturated sampling, where all respondents were taken at SMP Negeri 1 Koba, Central Bangka Regency. Data collection was carried out by distributing questionnaires using a 5-point Likert scale to measure 90 statement items. The analysis technique used is multiple linear regression analysis. The results showed that there was an influence of principal leadership and strategic implementation of digital-based school management on improving teachers' pedagogical competence Second, there was an influence of principal leadership on improving teachers' pedagogical competence Third, there was a strategic implementation of digital-based school management on improving teachers' pedagogical competence.